Color aberration in malachite kingfishers: Insights from community science observations in Queen Elizabeth National Park, Uganda - Bethany H. Warner; Katherine C. B. Weiss; Maximilian L. Allen (Ecology and Evolution)
Abstract Color aberrations in birds corresponds with important ecological functions, including thermoregulation and physiological impacts, camouflage and increased predation, and social interactions with conspecifics. Color aberrations in birds have been reported frequently in the scientific literature, but aberrations in many species remain undocumented or understudied. We investigated records of leucism in malachite kingfishers (Corythornis cristatus) from observations of community scientists on iNaturalist and eBird in Uganda. Leucistic kingfishers were only observed within the Queen Elizabeth National Park (QENP), Uganda. When considering all observations of malachite kingfishers that included photographs within the QENP, leucistic individuals accounted for 13.0% and 10.4% of total malachite kingfisher observations within the study area from iNaturalist and eBird, respectively. Leucistic observations were recorded from September 2015 through February 2017, making up 60.0% and 68.2% of observations of malachite kingfishers within the study area from iNaturalist and eBird during that time, respectively. The localized and short documentation period suggests observations represent a single individual, while the high observation rate likely corresponds with collection bias due to the novelty of the individual. Our findings help to better understand the ecological importance and potential consequences for color‐aberrant individuals, although color aberration did not appear to inhibit our subject's ability to find a mate. Our work also highlights how participatory science can promote the documentation of color‐aberrant individuals in wild populations, although it poses challenges when trying to estimate abundance.